2021
DOI: 10.2341/20-253-l
|View full text |Cite
|
Sign up to set email alerts
|

Handling and Mechanical Properties of Low-viscosity Bulk-fill Resin Composites

Abstract: SUMMARY This study aimed to evaluate the filler contents (FCs), flexural properties, depth of cure (DOC), wear resistance, and handling properties of different low-viscosity bulk-fill resin composites (LVBRCs) and to determine the correlations between the tested parameters. Six LVBRCs, Beautifil-Bulk (BBF), Bulk Base Hard (BBH), Bulk Base Medium (BBM), Filtek Bulk-Fill Flowable Restorative (FBF), G-ænial Bulk Injectable (GBI), and SDR flow+ Bulk-Fill Flowable (SDR) were used. The DOC and flexura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Most studies included in this systematic review reported mean flexural strength values above 80 MPa ( Table 7 ), fulfilling the requirements of the ISO 4049 standard [ 12 ] for type-1 resin composite materials. Among the reported flowable BF-RBC, the highest values were obtained by X-tra base (139.4 MPa) [ 24 ], G-aenial Bulk Injectable (143.9 MPa) [ 25 ] and Filtek Bulk Fill Flow (144.9 MPa) [ 26 ]. On the other hand, only four studies reported flexural strength values below the 80 MPa threshold [ 6 , 26–28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies included in this systematic review reported mean flexural strength values above 80 MPa ( Table 7 ), fulfilling the requirements of the ISO 4049 standard [ 12 ] for type-1 resin composite materials. Among the reported flowable BF-RBC, the highest values were obtained by X-tra base (139.4 MPa) [ 24 ], G-aenial Bulk Injectable (143.9 MPa) [ 25 ] and Filtek Bulk Fill Flow (144.9 MPa) [ 26 ]. On the other hand, only four studies reported flexural strength values below the 80 MPa threshold [ 6 , 26–28 ].…”
Section: Resultsmentioning
confidence: 99%